An empirical study on ‘how to retain rural teachers with emphasis on hygiene or motivation factors’: A case of Western China - Jiang, Jin-Qiu; Yao, Jie; Yu, Kai-Rui; Li, Chong-Nan (Frontiers in Psychology, 2023)
How to retain prominent teachers is the key problem for rural education in a less developed country. According to Herzberg's motivation-hygiene theory, this paper investigates 973 rural teachers in Western China by the Multi-step stratified sampling method, and studies the effects of hygiene factors (rural incentive policy, personnel policy, and teacher pay), motivation factors (advancement, work itself, and achievement) on teachers' turnover intention and the moderation effects of gender, age, marital status and teaching subjects on turnover intention. The results show that both hygiene factors and motivation factors can significantly reduce the turnover intention of rural teachers in Western China. At the same time, the effect of motivation factors is greater than that of hygiene factors. Marital status , age, and teaching subjects have a significant moderating effect on the relationship between motivation/hygiene factors and turnover intention, while gender has no significant moderating effect on turnover intention. Based on the above results, it is suggested that policymakers should design reasonable and flexible personnel policies for rural teachers, pay attention to the motivation and hygiene needs of unmarried teachers and English and art teachers, including career development, recognition, and incentive, and provide more internal growth opportunities for rural teachers.